Perancangan dan Pembuatan Aplikasi Penyusunan Jadwal Kerja Dinas Jaga Perawat IGD Menggunakan Algoritma TPB - Susandi, Dony; Milana, Lia (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
A hospital has an installation services including outpatient, inpatient, ER and laboratories. In making the case in the ER department schedules, lack of attention to equity aspects schedule guard duty nurse. Nurse scheduling is one of the problems in health care organizations that are hard to solve. The number of patients who are not controlled, the seriousness of the patient's disease, absence and private demand for the holiday, including making a schedule for each nurse into working hours (shifts) different in the short term. Seeing those conditions, it is done using the ER nurse scheduling algorithm method Tibrewala, Phillipe and Brown (TPB). This method can produce a schedule to minimize the amount of labor. In this research is also developing software for web-based application scheduling algorithm based on TPB.Making an application based on Data Flow Diagrams (DFD) is simple, consisting of one admin as manager application. Scheduling resulting from the processing of nurses to determine the needs, the number of nurses and the number of shift each nurse. The structure of application is made simple program consisting of, the need for nurses, shift work and the needs of the iteration process to generate schedules. Scheduling algorithms using the TPB can result in the division of labor and the amount of work shift power evenly to each nurse. This application help the process of scheduling the event of changes relating to the scheduling so that the scheduling process can be done at any time by efficiently and effectively.